The Post-Human Author: Deconstructing Narrative Identity And Creativity In Ai-Generated Literary Works - Wirdatul Khasanah; Li Wei; Rustiyana Rustiyana (Journal of Humanities Research Sustainability, 2025)
Background. The emergence of artificial intelligence as a creative agent has fundamentally disrupted the human-centered paradigm of authorship in literary production. Recent advances in generative models such as GPT and other neural language systems have blurred the boundaries between human intention, machine output, and narrative authenticity. Purpose. This study aims to deconstruct the notion of the “post-human author” by examining how AI-generated literary works redefine narrative identity, creativity, and the ontology of authorship. Employing a qualitative meta-analytical method combined with post-structuralist textual analysis, the research synthesizes existing literature and conducts interpretive readings of selected AI-generated texts. Through Derridean deconstruction and Foucault’s concept of the “author-function,” this study explores how algorithmic creativity challenges the metaphysics of originality and intentionality. Method. Employing a qualitative meta-analytical method combined with post-structuralist textual analysis, the research synthesizes existing literature and conducts interpretive readings of selected AI-generated texts. Through Derridean deconstruction and Foucault’s concept of the “author-function,” this study explores how algorithmic creativity challenges the metaphysics of originality and intentionality. Results. The findings reveal that AI-generated literature destabilizes the humanist framework of creative agency , producing hybrid narratives where authorship becomes distributed, contingent, and collaborative between human and machine. However, this post-human creativity also exposes ethical and philosophical tensions related to authorship, ownership, and meaning-making. Conclusion. The study concludes that literary creation in the age of AI demands a reconfiguration of aesthetic and epistemic assumptions about what it means to “create,” inviting a new hermeneutics of reading that acknowledges the co-agency of the artificial and the human.